ANALISIS DIGITALISASI PEMASARAN BERBASIS SOSIAL MEDIA UNTUK MENINGKATKAN DAYA SAING USAHA KECIL MENENGAH (UKM) DI PEKALONGAN - Siti Nurhayati; Arum Ardianingsih (Fakultas Ekonomi Universitas Pekalongan, 2021)
Increasing the competitiveness of SMEs can be done in the aspect of marketing based on social media, because this marketing medium is most familiar to SME entrepreneurs. Pekalongan with around 22 thousand number of UKM players and scattered in trade centers. SME entrepreneurs must have marketing competitiveness so that SMEs can survive in the future. This research is a qualitative research with a phenomenological approach. Methods of data collection use observation, in-depth interviews and documentation. The analysis technique in this study uses the stage of data reduction, data presentation and then drawing conclusions. The result of the research shows that SMEs in the marketing aspect have started to switch to social media-based marketing. The marketing media chosen include facebook, Instagram, WhatsApp. SME entrepreneurs need to be given training in creating interesting and innovative product promotional content and videos to optimize the use of social media-based marketing so as to increase the competitiveness of SMEs.